Non-Performing Loans in Banking: Analyzing Risk Mitigation Failures and Reconstructing Legal Protection Frameworks - Teguh Ikhrawansyah S; Hasbuddin Khalid; S. Salle (Golden Ratio of Law and Social Policy Review, 2026)
This study aims to critically examine the persistence of non-performing loans within the banking system by analyzing the failures of credit risk mitigation and reconstructing the legal protection framework governing creditor–debtor relationships. The research departs from the assumption that credit default is not solely an economic phenomenon but also a legal and institutional problem rooted in regulatory fragmentation, weak enforcement mechanisms, and imbalanced contractual arrangements. To address this issue, the study employs a normative legal research method, utilizing statutory and conceptual approaches. The statutory approach is used to analyze relevant regulations on banking, contracts, and insolvency, while the conceptual approach explores legal doctrines related to risk mitigation, fairness, and legal protection. Data are analyzed using a descriptive-prescriptive technique, which not only explains the existing legal framework but also formulates normative recommendations for reform. The findings reveal that current risk mitigation practices are overly formalistic and heavily dependent on collateral, without sufficient consideration of debtor capacity and legal enforceability. At the same time, the legal framework demonstrates significant deficiencies, including contractual imbalance, fragmented regulations, and inefficient dispute resolution mechanisms, which collectively weaken both preventive and corrective responses to credit default. This study finds that the disconnection between risk management practices and legal protection frameworks exacerbates systemic vulnerabilities within the banking sector. Accordingly, this research proposes an integrated reconstruction of legal protection and credit risk mitigation, emphasizing balanced contractual standards, effective enforcement mechanisms, regulatory harmonization, and a justice-oriented legal framework. Such reconstruction is essential to ensure a more equitable, resilient, and sustainable banking system.